Suzuki and Heck cross‐coupling reactions using ferromagnetic nanoparticle‐supported palladium complex as an efficient and recyclable heterogeneous nanocatalyst in sodium dodecylsulfate micelles. (19th October 2016) - Bahrami, Kiumars; Khodaei, Mohammad M.; Meibodi, Farhat Sadat
Abstract : A novel heterogeneous Pd catalyst was synthesized by anchoring Pd(II) onto 4′‐(4‐hydroxyphenyl)‐2, 2′:6′, 2″‐terpyridine‐coated Fe3 O4 (FMNPs@TPy‐Pd). This catalyst has been demonstrated for the first time as a recoverable and reusable heterogeneous nanocatalyst in Suzuki and Heck cross‐coupling reactions. The catalyst is very easy to handle and is environmentally safe and economical. FMNPs@TPy‐Pd was characterized using transmission and scanning electron microscopies, X‐ray diffraction, and Fourier transform infrared and energy‐dispersive X‐ray spectroscopies. Abstract : A novel heterogeneous Pd catalyst was synthesized by anchoring Pd(II) onto 4′‐(4‐hydroxyphenyl)‐2, 2′:6′, 2″‐terpyridine‐coated Fe3 O4 (FMNPs@TPy‐Pd). This catalyst was demonstrated for the first time as a recoverable and reusable heterogeneous nanocatalyst in Suzuki and Heck cross‐coupling reactions. The catalyst is very easy to handle and is environmentally safe and economical. FMNPs@TPy‐Pd was characterized using various methods.